Evaluation of the most odour-active compounds in the peel oil of clementines (Citrus reticulata blanco cv. clementine). - Büttner, Andrea; Mestres, Montse; Fischer, Anja; Guasch, Josep; Schieberle, Peter (European Food Research and Technology, 2004)
In an extract of the peel from clementines, prepared by solvent extraction, 42 odour-active compounds were detected by application of an aroma extract dilution analysis and subsequently identified by using the respective reference odorants. Among them, by far the highest flavour dilution factors were determined for the flowery smelling linalool, the fatty smelling (E,E)-deca-2,4-dienal and the winelactone eliciting a sweet odour quality. These were followed by α-pinene, myrcene and octanal with pinetree-like, geranium leaf-like and citrus-like aromas. Among the 30 odour-active compounds identified, 11 aroma compounds are reported here for the first time as important contributors to clementine peel aroma, e.g. winelactone, (E,E)-nona-2,4-dienal, carvone, (Z)-hex-3-enal or tr–4,5-epoxy-(E)-dec-2-enal.